Actions, Photos and Political Practice: Anthropological Contributions to the Social Production of Politics - Julieta Gaztañaga (Íconos)
This article contributes to the literature on political practice through an anthropological analysis of public infrastructure projects in contemporary Argentina. We differentiate two socially significant perspectives for the actors involved: as political activists and the managers of public infrastructure projects. Reviewing both of these perspectives allows us to approach political work in relation to the social production of politics, and with that, break with the lens of hermeneutic cynicism through which public infrastructure projects are often viewed. The research on which this article draws is based on various ethnographic studies conducted between 1999 and 2014. Through the analysis presented in this article these studies are revisited in light of new research questions and focuses on the everyday practices of politics.